2019
DOI: 10.1021/acs.jchemed.9b00397
|View full text |Cite
|
Sign up to set email alerts
|

Green Chemistry Coverage in Organic Chemistry Textbooks

Abstract: This paper examines the current state of the implementation of green chemistry into organic chemistry textbooks. Content analysis of the 15 most used organic chemistry textbooks revealed that only 10 of them had any mention of green chemistry. In textbooks that contained mentions of green chemistry, it was mentioned on less than 1% of pages. Green chemistry topics mentioned include the 12 green chemistry principles, atom economy, greener solvents and reagents, recycling, biodegradable materials, renewable feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 27 publications
1
42
0
Order By: Relevance
“…78,79,80 The lack of green chemistry content in organic chemistry textbooks has been explored and it has been suggested that connections to societal issues and sustainability contribute to the development of leadership skills. 81 The existing literature in green chemistry can be used as a template to develop strategies to fully integrate sustainable polymers into the curriculum. The design elements used in capstone projects, which contribute tremendously to student development and creativity, should be considered for integrating sustainability concepts.…”
Section: Key Takeawaysmentioning
confidence: 99%
“…78,79,80 The lack of green chemistry content in organic chemistry textbooks has been explored and it has been suggested that connections to societal issues and sustainability contribute to the development of leadership skills. 81 The existing literature in green chemistry can be used as a template to develop strategies to fully integrate sustainable polymers into the curriculum. The design elements used in capstone projects, which contribute tremendously to student development and creativity, should be considered for integrating sustainability concepts.…”
Section: Key Takeawaysmentioning
confidence: 99%
“…This decision was founded on the premise that green chemistry is essential for the students' future careers, helps facilitate systems thinking, 1−6 and introduces meaningful learning. 7,8 However, with the onset of COVID-19, our plans were suddenly changed. On March 16th, 2020, we were forced to move to an entirely online instructional model.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the spring of 2020, we planned to incorporate various aspects of green chemistry into the majors’ Organic Chemistry II laboratory via several hands-on experiments. This decision was founded on the premise that green chemistry is essential for the students’ future careers, helps facilitate systems thinking, and introduces meaningful learning. , However, with the onset of COVID-19, our plans were suddenly changed. On March 16th, 2020, we were forced to move to an entirely online instructional model.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing importance of green chemistry relating to materials, polymers, and polymer design in our global economy, there are few postsecondary courses that directly address material and polymer synthesis, function, and design, a key component to developing alternative “green-focused” chemistry. Instead, polymer chemistry is typically addressed in materials chemistry courses or organic chemistry courses as a subtopic . Due to the increasing popularity of polymer chemistry, postsecondary classrooms are expanding to include more information on their synthesis, function, and design.…”
Section: Introductionmentioning
confidence: 99%